Narrating and Negotiating the Repressed City: Representations of Prague in Jiri Weil's Work - Solic, Mirna (Bohemica Olomucensia, 2015)
By playing with the conventions of representations of urban space of Prague, Jiri Weil's novels Life with a Star and Mendelssohn is on the Roof represent a specific, yet insufficiently explored, contribution to the scholarship mapping Prague texts in literature. Their main feature is the extent to which Prague as a city is constructed as an easily recognizable, and perhaps expected, topos, with all of its cultural and historical significance for the establishment of the national and cultural identity.
Keywords: Novels by Jiri Weil; category of space; literary representation; topos of Prague